Pengaruh Pendidikan Seksualitas Komprehensif dalam Meningkatkan Kontrol Diri Seksual Pada Remaja Perempuan - Lanus, Esiria; Soetjiningsih, Christiana Hari; Murti, Heru Astikasari Setya (Bulletin of Counseling and Psychotherapy, 2024)
This study aims to examine the effect of Comprehensive Sexuality Education (CSE) on the improvement of sexual self-control among female adolescents in Kupang Tengah District, Indonesia. The participants in this study were 40 female adolescents aged 15-18 years, who had a boyfriend and had never engaged in sexual intercourse. The research used an experimental design with random assignment. Sexual self-control was measured using the Perceived Sexual Control (PSC) scale, which has a Cronbach's alpha coefficient of 0.869. The results of the independent t-test showed a two-tailed significance value of 0.000 (p < 0.05), with a t-value of 4.693 > t-table = 2.024. The average sexual self-control in the experimental group (M = 56.70) was higher than that of the control group (M = 54.20), indicating that CSE significantly influences the improvement of sexual self-control among adolescents.